Classes Of Interval-Valued Fuzzy Relational Inference Templates - Meng, Yew Kok; Kohout, L. J (Malaysian Journal of Computer Science, 1996)
In this paper, we present the various classes of inference templates which can be instantiated for making inferences in a fuzzy relational inference scheme. These templates are interval-valued and they capture the upper and lower bounds of fuzzy inference using point data. We present five classes of interval-valued inference templates which can be instantiated with bounded fuzzy connectives.